Ischemic Duration and Frequency Determines AKI-to-CKD Progression Monitored by Dynamic Changes of Tubular Biomarkers in IRI Mice - Dong, Yang; Zhang, Qunzi; Wen, Jiejun; Chen, Teng; He, Li; Wang, Yiyun; Yin, Jianyong; Wu, Rui; Xue, Rui; Li, Shiqi; Fan, Ying; Wang, Niansong (Frontiers in Physiology, 2019)
Ischemia reperfusion injury (IRI) is one of the most common causes of acute kidney injury (AKI). However, the pathogenesis and biomarkers predicting the progression of IRI-induced AKI to chronic kidney disease (CKD) remain unclear. A side-by-side comparison between different IRI animal models with variable ischemic duration and episodes was performed. The dynamic changes of KIM-1 and NGAL continuously from AKI to CKD phases were studied as well. Short-term duration of ischemia induced mild renal tubule-interstitial injury which was completely reversed at acute phase of kidney injury, while long-term duration of ischemia caused severe tubular damage, cell apoptosis and inflammatory infiltration at early disease stage, leading to permanent chronic kidney fibrosis at the late stage. Repeated attacks of moderate IRI accelerated the progression of AKI to CKD. Different from serum and urine levels of KIM-1 that increased at acute phase of IRI then declined gradually in chronic phase, NGAL increased continuously during AKI-to-CKD transition. Severity and frequency of ischemia injury determines the progression and outcome of ischemia-induced AKI. Inflammation, apoptosis and fibrogenesis likely participate in the progression of AKI to CKD. Both KIM-1 and NGAL enable noninvasive and early detection of AKI, but NGAL is associated better with the process of AKI-to-CKD progression.